Representing East Germany since unification : from colonization to nostalgia - Cooke, Paul, 1969- 1969- (Berg, 2005)
Cooke maps out the problematic path of German national identity as it struggles to deal with the legacy of division. Drawing on postcolonial theory, he argues that the East has been defined as the West's exotic other and shows how this stereotype has been vigorously challenged.